Comparative study on technical efficiency of mechanized and traditional rice farm in Nepal - Acharya, Prakash; Regmi, Punya Prasad; Gauchan, Devendra; Bahadur, Dilli; Bahadur, Gopal (Nepal Journals Online, 2020)
The study was conducted among 274 mechanized and 220 traditional rice farms using multistage sampling technique to assess the technical efficiency in rice production among mechanized and traditional farmers in Jhapa, Sunsari and Bardiya districts. The Cobb-Douglas functional form of the stochastic production frontier was employed to obtain the technical efficiency in mechanized and traditional rice farms. The overall technical efficiency of the mechanized and traditional rice farm ranged from 40.31 to 92.23 and 31.21 to 85.02%t with the mean technical efficiency of 80.56 and 70.11% respectively. The scope of increasing output by adopting the technology adopted by the best performer was 19.44% in mechanized and 29.89% in traditional rice farm respectively. Majority of the farmers were operating at an efficiency level 70-80% and 60-70% in mechanized and traditional farms respectively. The average technical efficiency of mechanized rice farm was higher than that of traditional rice farm and the difference was significant. There was scope of increasing output through rational use of existing resources in both farm categories. Manures, chemical fertilizers had significant and positive effect to total yield of rice kg/ha. The effect of machine use to total yield of rice was positive and significant. Rice farms adopting machines were more technically efficient compared to traditional rice farm.